Phytol anti-inflammatory activity: Pre-clinical assessment and possible mechanism of action elucidation - Islam, Muhammad Torequl; Ayatollahi, Seyed Abdulmajid; Zihad, S. M. Neamul Kabir; Sifat, Nazifa; Khan, Md. Roich; Paul, Arkajyoti; Salehi, Bahare; Islam, Tawhida; Mubarak, Mohammad S.; Martins, Natália; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Phytol (PHY) is an acyclic natural diterpene alcohol and a chlorophyll constituent that exhibits several pharmacological effects, such as anticancer, antioxidant, and antimicrobial. Here, we aimed to assess the PHY anti-inflammatory effect in vitro and in vivo, and to deepen knowledge on the possible mechanism of action. For this purpose, egg albumin (in vitro) test was performed by using acetyl salicylic acid (ASA) as a standard nonsteroidal anti-inflammatory drugs (NSAID). For in vivo test, male Wistar albino rats were treated (intraperitoneally) with 100 mg/kg of PHY and/or standard NSAIDs ASA (100 mg/kg) and diclofenac sodium (Diclo-Na, 10 mg/kg) to evaluate the combined effect of PHY in formalin-induced paw edema model. Furthermore, an in silico (CADD) study was accomplished to assess the effect of PHY against cyclooxygenase (COX)-1 and 2 enzymes, nuclear factor kappa B (NF-ÎºB), and interleukin-1Î² (IL-1Î²). Results revealed that PHY exhibits dose-dependent anti-inflammatory effect using the egg albumin method. PHY (100 mg/kg) co-treated with ASA and/or Diclo-Na reduced paw edema better than PHY alone or NSAIDs individual groups. Computational study showed that PHY efficiently interacts with COX-1 and 2, NF-ÎºB, and IL-1Î². In conclusion, PHY exhibits anti-inflammatory activity, possibly via COX-1 and 2, NF-ÎºB, and IL-1Î² dependent pathways.